Method for preparing amorphous carbon film on rubber surface, amorphous carbon film material and application
By forming a carbon plasma modified layer with a mesh structure on the rubber surface and gradually transforming it into a dense amorphous carbon film, the problem of poor bonding force between the amorphous carbon film and the rubber surface is solved, and the wear resistance and service life of the rubber are improved.
Patent Information
- Application Number
- CN202410091309.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-22
- Publication Date
- 2025-07-22
AI Technical Summary
In the prior art, the amorphous carbon film has poor bonding force with the film-based film surface on the rubber surface, which leads to prone to failure in a frictional environment, affecting the service life of the rubber.
After the rubber matrix is etched by inert ion beam, a carbon plasma modified layer with a mesh structure is formed on the rubber surface by plasma treatment, and carbon plasma is generated by glow discharge of graphite target, which is gradually converted into a deposition effect to form a dense amorphous carbon film.
It realizes the reliable combination of amorphous carbon film on the rubber surface and improves the service life of rubber in friction environments.
Smart Images

Figure CN120349555A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of polymer surface protection, and relates to a method for preparing an amorphous carbon film, specifically to a method for preparing an amorphous carbon film on the surface of rubber, as well as the obtained amorphous carbon film material and its uses. Background Art
[0002] Rubber is widely used in products such as tires, conveyor belts, and sealing rings. However, under heavy-duty dry friction conditions, it is prone to severe wear, reducing the service life of rubber and posing a safety hazard to the damage of service parts.
[0003] According to research, amorphous carbon films have lubricity and wear resistance. Therefore, many scholars have tried to prepare amorphous carbon films on the surface of rubber applied in friction environments to improve the wear resistance of rubber. Among them, amorphous carbon films are films composed of carbon elements and have an amorphous structure with irregular atomic arrangements. Amorphous carbon films can be prepared by methods such as chemical vapor deposition and magnetron sputtering. Different preparation processes will lead to differences in the structure of amorphous carbon films, thereby affecting their structure and various properties. Usually, to address the problem of strengthening the bonding force between the amorphous carbon film and the rubber surface, researchers use methods such as doping heteroelements, adding a transition layer at the film-substrate interface, applying an appropriate bias voltage, and pre-treating the substrate material. However, no matter which of the above methods is used, the a-C film prepared on the rubber surface always has a sudden transition from the carbonaceous structure of the rubber surface to the amorphous carbonaceous structure. When this mutated interface is subjected to external forces, it is prone to failure, resulting in weak film-substrate bonding strength.
[0004] Therefore, how to optimize the method for preparing amorphous carbon films and seek a new technology that can achieve reliable bonding of amorphous carbon films on the rubber surface has become the long-term research direction of industry researchers. Summary of the Invention
[0005] The main purpose of the present invention is to provide a method for preparing an amorphous carbon film on the surface of rubber, thereby overcoming the deficiencies of the prior art.
[0006] Another object of the present invention is also to provide an amorphous carbon film material and its uses.
[0007] To achieve the above object of the invention, the present invention adopts the following technical solutions:
[0008] The embodiment of the present invention provides a method for preparing an amorphous carbon film on the surface of rubber, which includes:
[0009] Performing inert ion beam etching treatment on the rubber matrix;
[0010] By using the plasma treatment method, glow discharge of the graphite target generates carbon plasma, which acts on the surface of the rubber matrix treated by inert ion beam etching to form a carbon plasma modified layer with a network structure;
[0011] Continue to make the graphite target generate carbon plasma by glow discharge, and continuously act on the surface of the rubber matrix with the carbon plasma modified layer to deposit and form a dense amorphous carbon film.
[0012] In some embodiments, the method includes: placing the rubber matrix treated by inert ion beam etching in a vacuum chamber, introducing an inert gas, using the graphite target as the target, applying a bias voltage to make the graphite target generate carbon plasma by glow discharge, and acting on the surface of the rubber matrix to form a carbon plasma modified layer with a network structure.
[0013] In some embodiments, the method includes: after the preparation of the carbon plasma modified layer is completed, continue to make the graphite target generate carbon plasma by glow discharge, and continuously act on the surface of the rubber matrix with the carbon plasma modified layer, gradually changing from the initial bombardment effect to the deposition effect, first generating an in-situ transformation layer, and then depositing and forming a dense amorphous carbon film.
[0014] The embodiment of the present invention also provides an amorphous carbon film material prepared by the foregoing method, which includes a rubber matrix, a carbon plasma modified layer, and an amorphous carbon film stacked in sequence.
[0015] The embodiment of the present invention also provides the use of the foregoing amorphous carbon film material in the protection of mechanical moving parts.
[0016] Compared with the prior art, the beneficial effects of the present invention are at least as follows:
[0017] The method for preparing an amorphous carbon film on the rubber surface provided by the present invention uses plasma to continuously bombard and treat the rubber surface, realizes the in-situ transformation of the organic polymer carbonaceous structure on the rubber surface or subsurface into an amorphous carbonaceous structure, so as to achieve the reliable bonding of the amorphous carbon film on the rubber surface. The amorphous carbon film and the rubber surface have excellent bonding properties, solve the problem of poor film-substrate bonding force of hard films prepared on the surface of flexible materials in the prior art, and improve the service life of rubber in a friction environment. Description of the Drawings
[0018] In order to more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the following will briefly introduce the drawings required for the description of the embodiments or the prior art. Obviously, the drawings in the following description are only some embodiments recorded in the present invention. For those of ordinary skill in the art, without creative efforts, other drawings can also be obtained based on these drawings.
[0019] Figure 1Schematic diagram of the structure of the amorphous carbon film on the rubber surface obtained in a typical embodiment of the present invention;
[0020] Figure 2 It is a cross-sectional scanning electron microscope (SEM) morphology diagram of the amorphous carbon film on the rubber surface obtained in Example 1 of the present invention;
[0021] Figure 3a It is a scanning electron microscope (SEM) morphology diagram of the wear scar of the amorphous carbon film on the rubber surface obtained in Example 1 of the present invention under an atmospheric environment;
[0022] Figure 3b It is a friction curve diagram of the amorphous carbon film on the rubber surface obtained in Example 1 of the present invention under an atmospheric environment;
[0023] Figure 4a It is a scanning electron microscope (SEM) morphology diagram of the wear scar of the amorphous carbon film on the rubber surface obtained in Example 2 of the present invention under an atmospheric environment;
[0024] Figure 4b It is a friction curve diagram of the rubber surface obtained in Example 2 of the present invention under an atmospheric environment;
[0025] Figure 5a It is a scanning electron microscope (SEM) morphology diagram of the wear scar of the amorphous carbon film on the rubber surface obtained in Example 3 of the present invention under an atmospheric environment;
[0026] Figure 5b It is a friction curve diagram of the rubber surface obtained in Example 3 of the present invention under an atmospheric environment;
[0027] Figure 6a It is a scanning electron microscope (SEM) morphology diagram of the wear scar of the amorphous carbon film on the rubber surface obtained in Example 4 of the present invention under an atmospheric environment;
[0028] Figure 6b It is a friction curve diagram of the rubber surface obtained in Example 4 of the present invention under an atmospheric environment;
[0029] Figure 7a It is a scanning electron microscope (SEM) morphology diagram of the wear scar of the amorphous carbon film on the rubber surface obtained in Example 5 of the present invention under an atmospheric environment;
[0030] Figure 7b It is a friction curve diagram of the rubber surface obtained in Example 5 of the present invention under an atmospheric environment;
[0031] Figure 8a It is a scanning electron microscope (SEM) morphology diagram of the wear scar of the amorphous carbon film on the rubber surface obtained in Example 6 of the present invention under an atmospheric environment;
[0032] Figure 8bIt is the friction curve of the rubber surface obtained in Example 6 of the present invention under the atmospheric environment;
[0033] Figure 9a It is the morphology diagram of the wear scar of the amorphous carbon film on the rubber surface obtained in Example 7 of the present invention under the atmospheric environment observed by scanning electron microscope (SEM);
[0034] Figure 9b It is the friction curve of the rubber surface obtained in Example 7 of the present invention under the atmospheric environment;
[0035] Figure 10a It is the morphology diagram of the wear scar of the amorphous carbon film on the rubber surface obtained in Comparative Example 1 of the present invention under the atmospheric environment observed by scanning electron microscope (SEM);
[0036] Figure 10b It is the friction curve of the rubber surface obtained in Comparative Example 1 of the present invention under the atmospheric environment;
[0037] Figure 11a It is the morphology diagram of the wear scar of the amorphous carbon film on the rubber surface obtained in Comparative Example 2 of the present invention under the atmospheric environment observed by scanning electron microscope (SEM);
[0038] Figure 11b It is the friction curve of the rubber surface obtained in Comparative Example 2 of the present invention under the atmospheric environment. Detailed implementation manners
[0039] In view of the defects of the prior art, through long-term research and a large number of practices by the inventors of this case, the technical solution of the present invention can be proposed. It mainly performs inert ion beam etching on the rubber matrix, prepares a carbon plasma modification layer on the matrix surface by the plasma treatment method, and then uses a graphite target glow discharge to generate carbon plasma, which continuously acts on the rubber surface, gradually changing from the initial bombardment effect to the deposition effect, first generating an in-situ transformation layer, and then forming a dense amorphous carbon film, which has excellent wear resistance under the atmospheric environment.
[0040] In order to further understand the present invention, the technical solution, its implementation process, principles, etc. will be further explained below. However, it should be understood that these descriptions are only for further explaining the features and advantages of the present invention, rather than limiting the claims of the invention.
[0041] Specifically, as an aspect of the technical solution of the present invention, a method for preparing an amorphous carbon film on a rubber surface mainly includes in sequence: performing inert ion beam etching on the rubber matrix, and then preparing a carbon plasma modification layer and an amorphous carbon film layer in sequence.
[0042] In some preferred implementation schemes of the present invention, the method for preparing an amorphous carbon film on the rubber surface includes:
[0043] The rubber matrix is subjected to inert ion beam etching treatment;
[0044] By using the plasma treatment method, the graphite target is subjected to glow discharge to generate carbon plasma, which acts on the surface of the rubber matrix treated by inert ion beam etching, and a carbon plasma modified layer with a network structure is prepared and formed on the surface of the rubber matrix;
[0045] Then, the graphite target continues to be subjected to glow discharge to generate carbon plasma, which continuously acts on the surface of the rubber matrix with the carbon plasma modified layer. The initial bombardment effect gradually changes to the deposition effect. First, an in-situ transformation layer (i.e., the carbon plasma modified layer) is generated, and then a dense amorphous carbon film is deposited and formed.
[0046] In some embodiments, the inert ion beam etching treatment in the method includes: placing the rubber matrix in a vacuum chamber, introducing an inert gas, applying an ion beam voltage and a bias voltage, and using inert plasma to perform the inert ion beam etching treatment on the surface of the rubber matrix.
[0047] In some preferred embodiments of the present invention, the inert ion beam etching treatment in the method may specifically include: placing the rubber matrix in a vacuum chamber and evacuating it. After reaching a certain vacuum pressure, introducing an inert gas, turning on the ion beam power supply, turning on the bias voltage power supply, and using inert plasma to perform the inert ion beam etching treatment on the surface of the matrix.
[0048] In some preferred embodiments of the present invention, the process conditions of the inert ion beam etching treatment include: the air pressure in the vacuum chamber is below 7.0×10 -3 Pa, the negative bias voltage is 300 - 600V, the duty cycle is 30 - 60%, the ion beam voltage is 600 - 1000V, the flow rate of the inert gas is 30 - 60 seem, and the time of the inert ion beam etching treatment is 10 - 30 min.
[0049] Furthermore, the rubber matrix can be any rubber, such as natural rubber, nitrile rubber, etc.
[0050] In some embodiments, the method for preparing the carbon plasma modified layer in the method includes: placing the rubber matrix treated by inert ion beam etching in a vacuum chamber, introducing an inert gas, using the graphite target as the target material, applying a bias voltage to make the graphite target glow discharge to generate carbon plasma, which acts on the surface of the rubber matrix to form a carbon plasma modified layer with a network structure.
[0051] In some preferred embodiments of the present invention, the method for preparing the carbon plasma modified layer may specifically include: after the inert ion beam etching treatment is completed, turn off the ion beam power supply. After reaching a certain vacuum pressure, introduce an inert gas into the vacuum chamber, turn on the graphite target power supply, and generate carbon plasma by the glow discharge of the graphite target, which acts on the surface of the rubber matrix.
[0052] In some preferred embodiments of the present invention, the process conditions of the plasma treatment method used for preparing the carbon plasma modified layer include: the air pressure in the vacuum chamber is below 7.0×10 -3 Pa, the negative bias voltage is 100 - 400V, the duty cycle is 30 - 60%, the graphite target current is 0.1 - 3.0A, the flow rate of the inert gas is 30 - 60 sccm, and the time for preparing the carbon plasma modified layer is 10 - 60 min.
[0053] In some embodiments, the method for preparing the amorphous carbon film specifically includes: after the carbon plasma modified layer is prepared, continue to generate carbon plasma by the glow discharge of the graphite target, and continuously act on the rubber matrix surface with the carbon plasma modified layer. It gradually changes from the initial bombardment effect to the deposition effect. The carbon plasma initially bombards the rubber surface and the sub-surface of the rubber to jointly form an in-situ transformation layer. After some time, the carbon plasma deposits on the basis of the in-situ transformation layer to form a dense amorphous carbon film. Among them, when the amorphous carbon film is prepared, the air pressure in the vacuum chamber is below 7.0×10 -3 Pa, the negative bias voltage is 100 - 400V, the duty cycle is 30 - 60%, the graphite target current is 0.1 - 3.0A, the flow rate of the inert gas is 30 - 60 sccm, and the deposition time is 0.5 - 5 h.
[0054] In summary, the process design of the amorphous carbon film on the rubber surface provided by the present invention solves the problem of poor film-substrate bonding force of the hard film prepared on the surface of flexible materials in the prior art, and improves the service life of the rubber in a friction environment. Specifically, the present invention uses plasma to continuously bombard and treat the surface of the rubber matrix to realize the in-situ transformation of the organic polymer carbonaceous structure on the rubber surface or sub-surface into an amorphous carbonaceous structure, so as to realize the reliable bonding of the amorphous carbon film on the rubber surface.
[0055] Another aspect of the embodiments of the present invention also provides an amorphous carbon film material prepared by the foregoing method. Specifically, the structural schematic diagram of the amorphous carbon film material prepared on the rubber matrix surface in the present invention is as Figure 1 shown, including a rubber matrix, a carbon plasma modified layer, and an amorphous carbon film stacked in sequence.
[0056] In some preferred embodiments, the carbon plasma modified layer is a network structure formed by crosslinking of the carbon plasma and the surface structure of the rubber matrix. This special structure enables the film to exhibit excellent wear resistance on the rubber surface.
[0057] In some preferred embodiments, the thickness of the carbon plasma modified layer is 5 - 20 nm.
[0058] In some preferred embodiments, the thickness of the amorphous carbon film is 100 - 500 nm.
[0059] In some preferred embodiments, the friction coefficient of the amorphous carbon film material in the atmospheric environment is 0.1 - 0.5, and the film material has excellent bonding with the surface of the rubber matrix.
[0060] Specifically, the friction coefficient of the amorphous carbon film on the surface of the rubber matrix in the atmospheric environment is about 0.2. The degree of friction and wear is smaller than that of the original rubber surface.
[0061] The amorphous carbon film material prepared on the surface of the rubber matrix in the present invention improves the film - substrate bonding force between the film and the rubber, and can play a positive role in extending the service life of the rubber.
[0062] Another aspect of the embodiments of the present invention also provides the use of the aforementioned amorphous carbon film material prepared on the surface of the rubber matrix in the protection of mechanical moving parts.
[0063] The technical solutions of the present invention will be further described in detail below in conjunction with several preferred embodiments and the accompanying drawings. These embodiments are implemented on the premise of the technical solutions of the present invention, and detailed implementation methods and specific operation processes are given. However, the protection scope of the present invention is not limited to the following embodiments.
[0064] The experimental materials used in the following embodiments can be purchased from conventional biochemical reagent companies without special instructions.
[0065] All the processes and equipment of the present invention have conventional names in the art, and each name is clear and definite in the relevant field of its use. Those skilled in the art can understand the conventional process steps and the corresponding equipment used according to the name.
[0066] Example 1
[0067] (1) Inspect the sample holder and the target of the equipment to ensure that the sample holder and the vacuum chamber, and the target and the vacuum chamber are in an insulating state. Inspect the gas path system to ensure that the gas path is unobstructed, and inspect the chiller system to ensure that the temperature inside the chamber is within a certain range.
[0068] (2) Fix the natural rubber substrate sample on the sample holder in the vacuum chamber of the deposition equipment, close the chamber, and evacuate to a vacuum degree in the chamber less than 7.0×10 -3 Pa.
[0069] (3) Introduce high-purity argon at a bias voltage of -400V and an ion beam voltage of 800V, with a duty cycle of 60% and an argon flow rate of 30 sccm, and perform target cleaning and substrate cleaning on the substrate for 15 minutes.
[0070] (4) Close the ion beam baffle, turn off the ion beam voltage and turn on the graphite target power supply. Set the current to 3.0A, the Ar flow rate to 60 sccm, the substrate negative bias voltage to 150V, and the duty cycle to 60% to prepare a carbon plasma modification layer, with a deposition time of 10 minutes.
[0071] (5) Set the sputtering current to 3.0A, the Ar flow rate to 60 sccm, the substrate negative bias voltage to 150V, and the duty cycle to 60% to prepare an amorphous carbon film, with a deposition time of 230 minutes.
[0072] The cross-sectional morphology of the amorphous carbon film on the surface of the natural rubber prepared in the above examples is as Figure 2 shown. It can be seen from Figure 2 that the thickness of the carbon plasma modification layer is about 15nm, and the thickness of the amorphous carbon film is about 500nm. Under a 1N load, the friction coefficient of the amorphous carbon film in the atmospheric environment is 0.33, and the friction contact surface is slightly damaged. The wear scar morphology diagram is as Figure 3a shown, and the friction curve diagram is as shown in Figure 3b.
[0073] Example 2
[0074] (1) Check the sample holder and target of the equipment to ensure that the sample holder and the vacuum chamber, and the target and the vacuum chamber are in an insulating state. Check the gas path system to ensure smooth gas flow, and check the chiller system to ensure that the temperature in the chamber is within a certain range.
[0075] (2) Fix the nitrile rubber substrate sample on the sample holder in the vacuum chamber of the deposition equipment, close the chamber, and evacuate to a vacuum degree in the chamber less than 7.0×10 -3 Pa.
[0076] (3) Introduce high-purity argon at a bias voltage of -400V and an ion beam voltage of 800V, with a duty cycle of 60% and an argon flow rate of 30 sccm, and perform target cleaning and substrate cleaning on the substrate for 15 minutes.
[0077] (4) Close the ion beam baffle, turn off the ion beam voltage, turn on the graphite target power supply, set the current to 3.0 A, the Ar flow rate to 60 sccm, the substrate negative bias voltage to 150 V, and the duty cycle to 60% to prepare a carbon plasma modified layer with a deposition time of 10 min.
[0078] (5) Set the sputtering current to 3.0 A, the Ar flow rate to 60 sccm, the substrate negative bias voltage to 150 V, and the duty cycle to 60% to prepare an amorphous carbon film with a deposition time of 50 min.
[0079] For the amorphous carbon film on the surface of nitrile rubber prepared in the above examples, the thickness of the carbon plasma modified layer is about 15 nm, and the thickness of the amorphous carbon film is about 100 nm. Under a 1 N load, the friction coefficient of the amorphous carbon film in the atmospheric environment is 0.33, the friction contact surface cracks but does not spall, and the wear scar morphology diagram is as Figure 4a shown, and the friction curve diagram is as shown in 4b.
[0080] Example 3
[0081] (1) Inspect the sample holder and target of the equipment to ensure that the sample holder and the vacuum chamber, and the target and the vacuum chamber are in an insulating state. Inspect the gas path system to ensure unobstructed gas flow, and inspect the chiller system to ensure that the chamber temperature is within a certain range.
[0082] (2) Fix the nitrile rubber substrate sample on the sample holder in the vacuum chamber of the deposition equipment, close the chamber, and evacuate to a vacuum degree less than 7.0×10 -3 Pa.
[0083] (3) Introduce high-purity argon at a bias voltage of -400 V and an ion beam voltage of 800 V, with a duty cycle of 60% and an argon flow rate of 30 sccm, and perform target cleaning and substrate cleaning on the substrate for 15 min.
[0084] (4) Close the ion beam baffle, turn off the ion beam voltage, turn on the graphite target power supply, set the current to 1.5 A, the Ar flow rate to 60 sccm, the substrate negative bias voltage to 150 V, and the duty cycle to 60% to prepare a carbon plasma modified layer with a deposition time of 10 min.
[0085] (5) Set the sputtering current to 1.5 A, the Ar flow rate to 60 sccm, the substrate negative bias voltage to 150 V, and the duty cycle to 60% to prepare an amorphous carbon film with a deposition time of 50 min.
[0086] In the above embodiments, the amorphous carbon film on the surface of the prepared nitrile rubber has an amorphous carbon plasma modification layer with a thickness of about 15 nm and an amorphous carbon film with a thickness of about 50 nm. Under a 1 N load, the friction coefficient of the amorphous carbon film in the atmospheric environment is 0.33, the friction contact surface cracks without peeling, and the wear scar morphology diagram is as shown in Figure 5a shown, and the friction curve diagram is as shown in Figure 5b.
[0087] Example 4
[0088] (1) Inspect the sample holder and target of the equipment to ensure that the sample holder and the vacuum chamber, and the target and the vacuum chamber are in an insulating state. Inspect the gas path system to ensure smooth gas flow, and inspect the chiller system to ensure that the temperature inside the chamber is within a certain range.
[0089] (2) Fix the nitrile rubber substrate sample on the sample holder in the vacuum chamber of the deposition equipment, close the chamber, and evacuate to a vacuum degree less than 7.0×10 -3 Pa.
[0090] (3) Introduce high-purity argon at a bias voltage of -400 V and an ion beam voltage of 800 V, with a duty cycle of 60% and an argon flow rate of 30 sccm, and perform 15 minutes of target cleaning and substrate cleaning on the substrate.
[0091] (4) Close the ion beam baffle, turn off the ion beam voltage and turn on the graphite target power supply. Set the current to 3.0 A, the Ar flow rate to 60 sccm, the substrate negative bias voltage to 150 V, and the duty cycle to 60% to prepare the amorphous carbon plasma modification layer, and the deposition time is 10 minutes.
[0092] (5) Set the sputtering current to 3.0 A, the Ar flow rate to 30 sccm, the substrate negative bias voltage to 150 V, and the duty cycle to 60% to prepare the amorphous carbon film, and the deposition time is 50 minutes.
[0093] In the above embodiments, the amorphous carbon film on the surface of the prepared nitrile rubber has an amorphous carbon plasma modification layer with a thickness of about 15 nm and an amorphous carbon film with a thickness of about 50 nm. Under a 1 N load, the friction coefficient of the amorphous carbon film in the atmospheric environment is 0.30, the friction contact surface cracks without peeling, and the wear scar morphology diagram is as shown in Figure 6a shown, and the friction curve diagram is as shown in Figure 6b.
[0094] Example 5
[0095] (1) Inspect the sample holder and target of the equipment to ensure that the sample holder and the vacuum chamber, and the target and the vacuum chamber are in an insulating state. Inspect the gas path system to ensure smooth gas flow, and inspect the chiller system to ensure that the temperature inside the chamber is within a certain range.
[0096] (2) Fix the natural rubber substrate sample on the sample holder in the vacuum chamber of the deposition equipment, close the chamber, and evacuate to a vacuum degree in the chamber less than 7.0×10 -3 Pa.
[0097] (3) Introduce high-purity argon under a bias voltage of -600V and an ion beam voltage of 800V, with a duty cycle of 45% and an argon flow rate of 30 sccm, and perform target cleaning and substrate cleaning on the substrate for 15 minutes.
[0098] (4) Close the ion beam baffle, turn off the ion beam voltage and turn on the graphite target power supply, set the current to 0.1A, the Ar flow rate to 30 sccm, the substrate negative bias voltage to 150V, and the duty cycle to 45% to prepare a carbon plasma modified layer, with a deposition time of 10 minutes.
[0099] (5) Set the sputtering current to 2.0A, the Ar flow rate to 60 sccm, the substrate negative bias voltage to 150V, and the duty cycle to 45% to prepare an amorphous carbon thin film, with a deposition time of 5 hours.
[0100] The cross-sectional morphology of the amorphous carbon thin film on the surface of natural rubber prepared in the above examples is as Figure 2 shown. It can be seen from Figure 2 that the thickness of the carbon plasma modified layer is about 15nm, and the thickness of the amorphous carbon thin film is about 100nm. Under a 1N load, the friction coefficient of the amorphous carbon thin film in the atmospheric environment is 0.50, and the friction contact surface is slightly damaged. The wear scar morphology diagram is as Figure 7a shown, and the friction curve diagram is as shown in Figure 7b.
[0101] Example 6
[0102] (1) Inspect the sample holder and target of the equipment to ensure that the sample holder and the vacuum chamber, and the target and the vacuum chamber are in an insulated state. Inspect the gas path system to ensure smooth gas flow, and inspect the chiller system to ensure that the temperature in the chamber is within a certain range.
[0103] (2) Fix the nitrile rubber substrate sample on the sample holder in the vacuum chamber of the deposition equipment, close the chamber, and evacuate to a vacuum degree in the chamber less than 7.0×10 -3 Pa.
[0104] (3) Introduce high-purity argon under a bias voltage of -400V and an ion beam voltage of 600V, with a duty cycle of 30% and an argon flow rate of 30 sccm, and perform target cleaning and substrate cleaning on the substrate for 30 minutes.
[0105] (4) Close the ion beam baffle, turn off the ion beam voltage, turn on the graphite target power supply, set the current to 2.0 A, the Ar flow rate to 60 sccm, the substrate negative bias voltage to 400 V, and the duty cycle to 30% to prepare a carbon plasma modified layer with a deposition time of 10 min.
[0106] (5) Set the sputtering current to 0.1 A, the Ar flow rate to 60 sccm, the substrate negative bias voltage to 400 V, and the duty cycle to 30% to prepare an amorphous carbon film with a deposition time of 30 min.
[0107] In the above examples, for the amorphous carbon film on the surface of nitrile rubber, the thickness of the carbon plasma modified layer is about 15 nm, and the thickness of the amorphous carbon film is about 50 nm. Under a 1 N load, the friction coefficient of the amorphous carbon film in the atmospheric environment is 0.44, the friction contact surface cracks but does not spall, and the wear scar morphology diagram is as Figure 8a shown, and the friction curve diagram is as shown in 8b.
[0108] Example 7
[0109] (1) Check the sample holder and target of the equipment to ensure that the sample holder and the vacuum chamber, and the target and the vacuum chamber are in an insulating state. Check the gas path system to ensure unobstructed gas flow, and check the chiller system to ensure that the chamber temperature is within a certain range.
[0110] (2) Fix the nitrile rubber substrate sample on the sample holder in the vacuum chamber of the deposition equipment, close the chamber, and evacuate to a vacuum degree less than 7.0×10 -3 Pa.
[0111] (3) Introduce high-purity argon gas at a bias voltage of -300 V and an ion beam voltage of 1000 V, with a duty cycle of 60% and an argon flow rate of 60 sccm, and perform 10 min of target cleaning and substrate cleaning on the substrate.
[0112] (4) Close the ion beam baffle, turn off the ion beam voltage, turn on the graphite target power supply, set the current to 0.5 A, the Ar flow rate to 30 sccm, the substrate negative bias voltage to 100 V, and the duty cycle to 60% to prepare a carbon plasma modified layer with a deposition time of 10 min.
[0113] (5) Set the sputtering current to 0.5 A, the Ar flow rate to 30 sccm, the substrate negative bias voltage to 100 V, and the duty cycle to 60% to prepare an amorphous carbon film with a deposition time of 30 min.
[0114] In the above embodiments, the thickness of the amorphous carbon film on the surface of the prepared nitrile rubber is about 15 nm, and the thickness of the amorphous carbon film is about 50 nm. Under a load of 1 N, the friction coefficient of the amorphous carbon film in the atmospheric environment is 0.36, the friction contact surface cracks but does not spall, and the wear scar morphology diagram is as shown in Figure 9a shown, and the friction curve diagram is as shown in Figure 9b.
[0115] Comparative Example 1
[0116] In this comparative example, natural rubber used in Example 1 was adopted. Under a load of 1 N, the friction coefficient of the surface of the natural rubber in the atmospheric environment is 0.53, the friction contact surface is severely worn, and the wear scar morphology diagram is as shown in Figure 10a shown, and the friction curve diagram is as shown in Figure 10b.
[0117] Comparative Example 2
[0118] In this comparative example, the nitrile rubber used in Example 2 was adopted. Under a load of 1 N, the friction coefficient of the surface of the nitrile rubber in the atmospheric environment is 0.86, the friction contact surface is severely worn, and the wear scar morphology diagram is as shown in Figure 11a shown, and the friction curve diagram is as shown in Figure 11b.
[0119] In addition, the inventor of this case also referred to the foregoing embodiments and conducted tests with other raw materials, process operations, and process conditions described in this specification, and all obtained relatively ideal results.
[0120] It should be understood that the technical solution of the present invention is not limited to the limitations of the above specific embodiments. Any technical deformation made according to the technical solution of the present invention without departing from the purpose of the present invention and the scope protected by the claims falls within the protection scope of the present invention.
Claims
1. A method for preparing an amorphous carbon film on the surface of rubber, characterized in that, Comprising: Performing inert ion beam etching treatment on a rubber matrix; Adopting a plasma treatment method to cause glow discharge of a graphite target to generate carbon plasma, which acts on the surface of the rubber matrix subjected to inert ion beam etching treatment to form a carbon plasma modified layer with a network structure; Continuing to cause glow discharge of the graphite target to generate carbon plasma, and continuously acting on the surface of the rubber matrix with the carbon plasma modified layer to deposit and form a dense amorphous carbon film.
2. The method according to claim 1, wherein Comprising: Placing the rubber matrix in a vacuum chamber, introducing an inert gas, applying an ion beam voltage and a bias voltage, and performing the above-mentioned inert ion beam etching treatment on the surface of the rubber matrix by using inert plasma.
3. The method according to claim 2, wherein The process conditions for the inert ion beam etching treatment include: the air pressure in the vacuum chamber is below 7.0×10 -3 Pa, the negative bias voltage is 300 - 600 V, the duty cycle is 30 - 60%, the ion beam voltage is 600 - 1000 V, the flow rate of the inert gas is 30 - 60 sccm, and the time for the inert ion beam etching treatment is 10 - 30 min.
4. The method according to claim 1, wherein Comprising: Placing the rubber matrix subjected to inert ion beam etching treatment in a vacuum chamber, introducing an inert gas, using the graphite target as a target material, applying a bias voltage to cause glow discharge of the graphite target to generate carbon plasma, which acts on the surface of the rubber matrix to form a carbon plasma modified layer with a network structure.
5. The method according to claim 4, characterized in that The process conditions of the plasma treatment method include: the air pressure in the vacuum chamber is below 7.0×10 -3 Pa, the negative bias voltage is 100 - 400 V, the duty cycle is 30 - 60%, the graphite target current is 0.1 - 3.0 A, the flow rate of the inert gas is 30 - 60 sccm, and the time for preparing the carbon plasma modification layer is 10 - 60 min.
6. The method according to claim 1, wherein Comprising: After the carbon plasma modification layer is prepared, continue to generate carbon plasma by glow discharge of the graphite target, and continuously act on the surface of the rubber matrix with the carbon plasma modification layer to deposit a dense amorphous carbon film. Among them, when the amorphous carbon film is prepared, the air pressure in the vacuum chamber is 7.0×10 -3 Pa or less, the negative bias voltage is 100-400V, the duty cycle is 30-60%, the graphite target current is 0.1-3.0A, the flow rate of the inert gas is 30-60sccm, and the deposition time is 0.5-5h.
9. An amorphous carbon film material prepared by the method according to any one of claims 1-6, which comprises a rubber matrix, a carbon plasma modified layer and an amorphous carbon film stacked in sequence.
8. The amorphous carbon thin film material according to claim 7, wherein: The carbon plasma modified layer is a network structure formed by cross-linking of carbon plasma and the surface structure of the rubber matrix; and / or, the thickness of the carbon plasma modified layer is 5-20 nm; and / or, the thickness of the amorphous carbon film is 100-500 nm.
9. The amorphous carbon thin film material according to claim 7, characterized in that: The friction coefficient of the amorphous carbon film material in an atmospheric environment is 0.1-0.
5.
10. Use of the amorphous carbon film material according to any one of claims 7-9 in the protection of mechanical moving parts.